Non-State Actors, Non-Consultative Parties and their Participation in the Antarctic Treaty Consultative Meetings - Ramirez Buchheister, Gustavo (My University, 2025)
Abstract To this day, the Antarctic Treaty is only open for accession by States, to the exclusion of any other actors in the international field lacking the quality of statehood; the Protocol for Environmental Protection has followed suit. States Parties, while equally bound by the Treaty, are divided into Consultative and Non-Consultative, with different levels of participation rights. The exception to this approach is the CAMLR Convention, which allows for the membership of regional economic integration organisations ( REIO s). Nevertheless, an evolution in the participation of actors other-than-Consultative Parties can be identified. This contribution focuses on the figures of Non-Consultative Parties, Observers and Experts to the Antarctic Treaty Consultative Meetings, addressing their incorporation and evolution in the System, as well as describing their characteristics and how they compare to the more general institution of “observership” in International Law.